QBD-BASED RP-UPLC METHOD DEVELOPMENT AND VALIDATION FOR THE SIMULTANEOUS ESTIMATION OF ATEZOLIZUMAB AND HYALURONIDASE IN CANCER DRUG FORMULATIONS - SREE, KONDURI JAYA; MUDHULKAR, RAJU; GUNDEKARI, SREEDHAR; KOTTAKKI, NAVEEN KUMAR; KONDURI, AMRUTHA SRI (International Journal of Applied Pharmaceutics, 2025)
Objective: Atezolizumab and hyaluronidase have been approved for subcutaneous injection for all adult indications as the intravenous formulation of atezolizumab, including non-small cell lung cancer (NSCLC), small cell lung cancer (SCLC), hepatocellular carcinoma (HCC), melanoma, and alveolar soft part sarcoma (ASPS). In this study, a new reverse-phase ultra-performance liquid chromatography (RP-UPLC) method was developed using a Quality by Design (QbD) approach for the simultaneous quantification of hyaluronidase (HYAL) and atezolizumab (ATEZ). Methods: The method optimisation was performed using a central composite design (CCD) in Design Expert Software, which offers a systematic framework for design of experiments (DOE), facilitating the evaluation of factor-response relationships and ensuring statistically significant results to enhance analytical quality. HYAL and ATEZ were successfully separated using a Waters ACQUITY UPLC HSS C18 Column (100 mm × 2.1 mm, 1.8 µm particle size) with an isocratic mobile phase consisting of trifluoroacetic acid buffer (pH 2.0) and acetonitrile in a 58:42% v/v ratio, at a flow rate of 0.3 ml/min. Results: In the developed UPLC method, HYAL and ATEZ were detected at 210 nm and 280 nm, respectively. The process was validated in compliance with ICH Q2 (R2) guidelines by evaluating key parameters such as system suitability, linearity, accuracy, precision, robustness, sensitivity, limit of detection (LOD), limit of quantification (LOQ) and analyte stability. The LOD and LOQ were determined using signal-to-noise ratios of 3:1 and 10:1, respectively, yielding values of 0.002 µg/ml (LOD) and 0.006 µg/ml (LOQ) for HYAL and 1.49 µg/ml (LOD) and 4.52 µg/ml (LOQ) for ATEZ, respectively. System suitability results demonstrated excellent reproducibility, with mean% RSD for the theoretical plate number and tailing factor across six replicate injections being 0.39% and 1.98% for HYAL and 0.22% and 0.38% for ATEZ, respectively. Conclusion: The QbD-based RP-UPLC method developed using central composite design enables precise, sensitive, and robust simultaneous quantification of atezolizumab and hyaluronidase. The technique showed efficient separation, excellent system suitability, and low LOD and LOQ values. Validation as per ICH Q2(R2) confirms its applicability for routine analysis and quality control of ATEZ-and HYAL-loaded nano-hydrogel formulations prepared by ionic gelation.